SYSTEM OF VOCATIONAL GUIDANCE WORK IN SECONDARY SCHOOL (Pedagogy of Higher and Secondary Education, 2008)
In this article the conception opens up of the system of vocational orientation work at school as organic component part of process of forming of personality of studying, expressed in presence definite knowledges, abilities and qualities personalities, necessary for the conscious choice of profession.